Survey on etiological diagnosis of diabetes in 1244 Italian diabetic children and adolescents: Impact of access to genetic testing. Issue 3 (March 2015) - Mozzillo, Enza; Salzano, Giuseppina; Barbetti, Fabrizio; Maffeis, Claudio; Lombardo, Fortunato; Franzese, Adriana; Delvecchio, Maurizio; Marigliano, Marco
Abstract Type 2 and monogenic diabetes are emerging causes of diabetes in youths. Among 1244 Italian patients <18 years of age, 91.9% had type 1, 0.2% type 2, and 4.9% monogenic diabetes. Monogenic diabetes ranks second as a cause of diabetes in Italian youth, while type 2 diabetes appears to be rare.